Selective reduction of alcohol drinking in Sardinian alcohol-preferring rats by a sigma-1 receptor antagonist - Sabino, Valentina (2009)
RATIONALE AND OBJECTIVES: Sigma receptors have been implicated in appetitive effects of psychostimulants and in high levels of ethanol intake. This study tested the hypothesis that the sigma-1 receptor subtype (Sig-1R) may modulate ethanol intake. MATERIAL AND METHODS: The effects of acute and repeated treatment with the potent, selective Sig-1R antagonist NE-100 on ethanol intake (10%) were studied in adult, male Sardinian alcohol-preferring (sP) rats, a model of genetic predisposition to high ethanol drinking. To assess the specificity of action, the acute effects of NE-100 on intake of an equally preferred sucrose solution and of a higher concentration of ethanol that sP rats did not prefer over water (28%), were determined. Finally, the ability of NE-100 administration to prevent the increased ethanol intake that occurs after deprivation was evaluated. RESULTS: Acute treatment with NE-100 dose-dependently (10–30 mg/kg) reduced 1- and 3-h intake of 10% ethanol solution in sP rats, while increasing concurrent water intake and not affecting food intake. NE-100 (17.8–30 mg/kg) comparably reduced intake of the 28% ethanol solution, while not suppressing 1.25% sucrose solution intake, suggesting selectivity of action against ethanol intake. Acute NE-100 (30 mg/kg) also prevented an increase in ethanol intake after a 7-day deprivation period. Repeated, daily NE-100 (30 mg/kg) treatment continued to reduce 24-h ethanol intake across 7 days of administration, with some, but incomplete, tolerance, evident by day 6. CONCLUSIONS: The results implicate the Sig-1R system in alcohol drinking, identifying a potential therapeutic target for the treatment of alcohol use disorders.